Treatment plan quality for stereotactic treatment of multiple cranial metastases: comparison of C-arm and O-ring treatment platforms - Shiba, Sakhele Lancelort (Stellenbosch : Stellenbosch University, 2025)
Shiba, S. L. 2025. Treatment plan quality for stereotactic treatment of multiple cranial metastases: comparison of C-arm and O-ring treatment platforms. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/2b3c144c-4368-4a18-8ec1-f3c311437392